Analisis Pembentukan Online Personal Branding Melalui Media Sosial (Studi Kasus Channel YouTube The Jooomers) - Japutra, Josephine Patricia; Winduwati, Septia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Along with the development of the gaming industry, namely, streaming games. The existence of the internet, technological advances and the use of social media such as YouTube have supported and encouraged game content creators to compete to be the audience's choice. One of them is by forming and maintaining personal branding on online platforms so that it can attract attention and leave an impression according to the desired perception. Therefore, this research aims to find out the online personal branding that has been implemented by one of the game content creators on YouTube, namely, The Jooomers, through content that has been uploaded to his YouTube channel in order to survive in the competitive game streaming market. Also, the perception that has been captured by the audience, especially subscribers regarding online personal branding. Researchers use the theories of mass communication, public relations, online personal branding, content creators and social media to examine this research. The method used is a descriptive qualitative approach through content observation and interviews with subscribers. Based on the research results, it is known that The Jooomers has fulfilled the Skill Set, Aura and Identity elements, thereby giving rise to the Brand Experience, First Impression and Getting Found elements that are obtained by its subscribers. Also, online personal branding is a practical strategy for content creators who want to create personal branding using any online platform. Meanwhile, content creators need to pay attention to relevance in realizing the aspects that make up online personal branding in practice so that the desired goals can be achieved. Seiring dengan perkembangan bidang industri game yakni, streaming game. Eksistensi kemajuan teknologi hingga penggunaan media sosial seperti YouTube telah mendukung sekaligus mendorong content creator game harus bersaing untuk menjadi pilihan audiens. Salah satunya dengan membentuk dan menjaga personal branding pada platform online agar dapat menarik perhatian dan meninggalkan kesan sesuai dengan persepsi yang diinginkan. Penelitian ini bertujuan untuk mengetahui online personal branding yang telah diterapkan oleh salah satu content creator game di YouTube yakni, The Jooomers melalui konten yang telah diunggah pada kanal YouTubenya agar dapat bertahan pada kompetisi pasar streaming game. Serta, persepsi yang telah ditangkap oleh audiens, terutama subscriber-nya terhadap online personal branding tersebut. Peneliti menggunakan teori komunikasi massa, public relations, online personal branding, content creator dan media sosial untuk mengkaji penelitian ini. Metode yang digunakan adalah pendekatan kualitatif deskriptif melalui observasi konten dan wawancara dengan subscriber-nya. Berdasarkan hasil penelitian diketahui bahwa The Jooomers telah memenuhi elemen Skill Set, Aura dan Identity hingga memunculkan elemen Brand Experience, First Impression dan Getting Found yang diperoleh subscriber-nya. Serta, online personal branding merupakan strategi praktis untuk dilakukan oleh content creator yang ingin membentuk personal branding yang memanfaatkan platform online apapun. Adapun content creator perlu memperhatikan relevansi dalam mewujudkan aspek-aspek yang membentuk online personal branding pada praktiknya agar tujuan yang diinginkan dapat tercapai.